PENGARUH BERBAGAI JENIS DAN KONSENTRASI PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL KACANG PANJANG - Djatmiko, Djatmiko; Rustianti, Sri; Sajadi, Sajadi (University of Prof. Dr. Hazairin, SH, 2015)
This study aims to determine the effect of various types and concentrations of organic fertilizers on growth and yield of beans. Research conducted at the village Margosari, Ilir subdistrict Talo Seluma, in September 2015 until January 2016. This study was a completely randomized block design, arranged as factorial. Consists of two factors: the first is a kind of liquid organic fertilizer (P) consists of four treatments namely: P1 = Liquid Organic Fertilizer Hantu; P2 = Organic Fertilizer Crystal Sampurna; P3 = Liquid Organic Fertilizer Biotrent; P4 = Liquid Organic Fertilizer Biotama. The second factor is the concentration of liquid organic fertilizer (K) consists of four treatments namely: K0 = Control; K1 = concentration of 1 ml / l of water; K2 = 2 ml / l of water; K3 = 3 ml / l of water. Each combination treatment was repeated 3 times.The study concluded (1) The treatment of liquid organic fertilizers and the interaction between the type and concentration of organic fertilizers no real effect on the growth and yield of beans, while the concentration of organic liquid fertilizer treatments was highly significant. (2) The concentration of liquid organic fertilizer 3 ml / l of water deliver growth and long beans optimal results.Keywords: organic fertilizers,beans, types and concentrations